Tameika Struggles To Face The Beauty Standard In Ashley Franklin’s Not Quite Snow White - Munajat, Hanna Puspita; Nursiah, Hamidah; Sapira, Intan; Andani, Shelly Audita (CV. ITTC INDONESIA, 2023)
This study aims to reveal the beauty construction issue depicted in the picture book Not Quite Snow White. The concept of beauty is a social construction aimed at women. This concept makes women obsessed with beauty which often makes discrimination against people who do not fit the beauty standards and makes special treatment for those who do. This particular treatment is called beauty privilege—the issue in the picture book story Not Quite Snow White is related to the author's background. Ashley Franklin is an African-American woman who does not fit the beauty standards established by society. She is not white, not slim, and has no fair skin. This study illustrates how the concept of beauty is built in society and how characters in the picture book story Not Quite Snow White break that standard of beauty and proof that beauty is a myth. This study uses the descriptive qualitative method and applies the theory of the beauty myth by Naomi Wolf to support the data in this study. The study results show a beauty standards construction that refers to skin color, body shape, and hairstyle addressed to the main character in this story, a girl named Tameika.